2021
DOI: 10.1088/1742-6596/1999/1/012057
|View full text |Cite
|
Sign up to set email alerts
|

Radioactivity Investigation In Water of Tigris River in Salah Al-Din Governorate, Iraq

Abstract: The spacific activity of naturally radionuclides (226Ra, 212Pb, and 40K) in water samples of Tigris river was tested using a NaI(Tl) scintillation detector at 30 separate locations in tigris river in Iraq’s Salah Al-Din Governorate. The activity concentrations of activity of 226Ra, 212Pb, 137Cs, and 40K ranged from ( 0.056, 0.702, 0.15, 105.12 Bq/L ) to ( 805.6, 75.12, 27.6, 1149.4 Bq/L ), with an average of ( 315.6, 30.8, 12.04, and 509.2 Bq/L) respectively. The average The radium equivalent activity was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The samples were filtered with filter paper to remove suspended particles and acidified to a pH of ≤ 2 using HNO3 drops. The samples were then filled in sealed 1.4-L Marinelli containers 11 , 12 .
Figure 1 Sampling sites along Nile River from Qena governorate, south Egypt (ArcGIS software 10.8.1; ArcGIS Online).
…”
Section: Methodsmentioning
confidence: 99%
“…The samples were filtered with filter paper to remove suspended particles and acidified to a pH of ≤ 2 using HNO3 drops. The samples were then filled in sealed 1.4-L Marinelli containers 11 , 12 .
Figure 1 Sampling sites along Nile River from Qena governorate, south Egypt (ArcGIS software 10.8.1; ArcGIS Online).
…”
Section: Methodsmentioning
confidence: 99%
“…[10] It was found that the water temperature ranged between 12.5 -28.5 Cº in the Tigris-Tikrit River. [11] indicated that the water temperature ranged between 10-25 Cº in the Tigris-Tikrit River in the area between Al-Hamra and Al-Zalaya. The water temperature of the Tigris River in the area between Al-Mahzam and Al-Zalaya ranged from( 10-25) ° C [12 [ 6 ] It was found that the water temperature of the Tigris River north and south of Samarra Dam ranged between 9-30 °C and the lowest degree was in January.…”
Section: Physical and Chemical Propertiesmentioning
confidence: 99%
“…[10] found that it ranged between 6.7-8.0 in the Tigris-Tikrit River. [11] recorded pH values that ranged between 6.3-8.3. [12] indicated that its range ranged between 6.3 -8.5 for the waters of the Tigris River in the area confined between the Al-Mahzam area to Al-Zalaya.…”
Section: Phmentioning
confidence: 99%
See 1 more Smart Citation